INFRARED SPECTRAL ANALYSIS OF THE IONITE BASED ON DIMETHYLOLCARBAMIDE AND ORTHOPHOSPHORIC ACID AND ITS COMPLEX WITH MERCURY (II) ION (Journal of Universal Science Research, 2025)
This study investigates the infrared (IR) spectra of an ionite synthesized from dimethylolcarbamide and orthophosphoric acid and its complex formed with mercury (II) ion. The presence of functional groups in the ionite and spectral changes after the formation of the complex were analyzed. Based on the results obtained, conclusions were drawn about the ionite’s selectivity toward metal ions and the complexation mechanism.